The role of emotion regulation in body-focused repetitive behaviours. (30th March 2016) - Roberts, Sarah; O'Connor, Kieron; Aardema, Frederick; Bélanger, Claude; Courchesne, Catherine
Abstract: Body-focused repetitive behaviours (BFRBs) including trichotillomania, skin picking, and nail biting, are non-functional self-destructive habits, which have a severe negative impact on everyday functioning. Although BFRBs cause distress, they are maintained by both negative (relief) and positive (stimulation) reinforcement. The emotional regulation (ER) model proposes that people with BFRBs have a general deficit in ER and, as a consequence, engage in BFRBs to alleviate affect and reinforce the behaviour. The current study was designed to explore differences in ER between people with BFRBs and controls to identify specific emotions triggering BFRBs. Forty-eight participants (24 BFRB, 24 controls) completed questionnaires measuring Difficulties in Emotional Regulation (DERS), a Triggers Scale and an Affective Regulation Scale (ARS). Significant differences in people with BFRBs and controls were reported principally on the DERS subscales of lack of emotional clarity, difficulties in impulse control, and access to ER strategies. On the ARS, the BFRB group reported overall difficulty 'snapping out' of emotions. The majority of BFRBs were reported to be triggered by anxiety (78%), tension (70%), or boredom (52%). The clinical implication is that ER could be beneficially targeted in therapy for BFRBs.